2022
DOI: 10.7150/thno.76873
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Kras and mTOR crosstalk drives hepatocellular carcinoma development via PEG3/STAT3/BEX2 signaling

Abstract: Background & Aims: Abnormal activation of mTOR through loss of tuberous sclerosis complex (Tsc) frequently occurs in hepatocellular carcinoma (HCC). Mutant Kras could induce aggressive HCCs. Here, we aim to identify the predictive or prognostic biomarkers for HCC patients with Kras mutant and mTOR hyperactivation, and to provide potential therapeutic approaches for this subtype of HCCs. Methods: We generated transgenic mice in which hepatocytic mTOR was hyperactivated through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…Additionally, some genes used to model SLC scores have also been studied in gastric and other cancers. Particularly, high expression levels of RBPMS2 , 31 DZIP1 , 32 PEG3 , 33 TSPYL5 34 and MAGEA4 35 , 36 in gastric cancer or other tumour tissues have been associated with a poor prognosis, while high expression levels of CXCL3 and TNFRSF11A in gastric cancer have been associated with a better prognosis 37 , 38 ; these observations are consistent with our findings. Thus, the clinical translational potential of SLC family gene members can be realized using the SLC score, which has good reproducibility and clinical applicability for predicting prognosis and guiding therapeutic strategies.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, some genes used to model SLC scores have also been studied in gastric and other cancers. Particularly, high expression levels of RBPMS2 , 31 DZIP1 , 32 PEG3 , 33 TSPYL5 34 and MAGEA4 35 , 36 in gastric cancer or other tumour tissues have been associated with a poor prognosis, while high expression levels of CXCL3 and TNFRSF11A in gastric cancer have been associated with a better prognosis 37 , 38 ; these observations are consistent with our findings. Thus, the clinical translational potential of SLC family gene members can be realized using the SLC score, which has good reproducibility and clinical applicability for predicting prognosis and guiding therapeutic strategies.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the PI3K/Akt signaling pathway is worth exploring. Meanwhile, it was found that the role of KRAS protein in the early stage of tumor development has always been a focus of attention, [ 41–43 ] but its mechanism in the fibrosis stage was still unclear. The occurrence and development of LF are often accompanied by oxidative stress, which is defined as the imbalance between free radicals and reactive metabolites, playing an important role in the pathogenesis of LF and being eliminated by the antioxidant system.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effectiveness of these therapies can be influenced by various factors, including the genetic background of the tumour and the tumour's microenvironment 33 . KRAS is an oncogene involved in cell signalling pathways that regulate proliferation, differentiation and survival 34 . In HCC, KRAS mutations are rare but its pathway can be activated via other mechanisms, contributing to tumour development and progression 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…33 KRAS is an oncogene involved in cell signalling pathways that regulate proliferation, differentiation and survival. 34 In HCC, KRAS mutations are rare but its pathway can be activated via other mechanisms, contributing to tumour development and progression. 35,36…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation